Effects of Light Intensity on Root Development in a D-Root Growth System - Miotto, Yohanna Evelyn; da Costa, Cibele Tesser; Offringa, Remko; Kleine-Vehn, Jürgen; Maraschin, Felipe dos Santos (Frontiers in Plant Science, 2021)
Plant development is highly affected by light quality, direction and intensity. Under natural growth conditions, shoots are directly exposed to light whereas roots develop underground shielded from direct illumination. Photomorphogenic development strongly represses shoot elongation whereas promotes root growth. Over the years, several studies helped the elucidation of signaling elements that coordinate light perception and underlying developmental outputs. Light exposure of the shoots has diverse effects on main root growth and lateral root formation. Here, we evaluated phenotypic root responses of wild-type Arabidopsis plants, as well as several mutants, grown in a D-Root system. We observed that sucrose and light act synergistically to promote root growth and that sucrose alone cannot overcome the light requirement for root growth. We also show that roots respond to the light intensity applied to the shoot by changes in primary and lateral root development. Loss-of-function mutants for several root light-response genes display varying phenotypes according to the light intensity to which shoots are exposed. Low light intensity strongly impaired lateral root development for most genotypes. Only vid-27 and pils4 mutants showed higher lateral root density at 40 μmol m−2 s−1 than at 80 μmol m−2 s−1 whereas yuc3 and shy2-2 presented no lateral root development in any light condition, reinforcing the importance of auxin signaling in light-dependent root development. Our results support the use of D-Root systems to avoid the effects of direct root illumination that might lead to artifacts and unnatural phenotypic outputs.